Asosiasi Antara Situasi Emosi, Kepatuhan Pada Oral Anti Diabetes, dan Hemoglobin Terglikasi Pada Penyandang Diabetes Mellitus Tipe 2 - Inge Wattimena; Galuh Nawang Prawesti (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
The problem of diabetes, which is predicted to increase in number of people suffering from diabetes in the upcoming years, needs to be examined from a bio-psycho-social perspective. This chronic illness which is difficult to be cured, affects the emotional situation and also the adherence to oral anti-diabetes (OAD). The objective of this study is to examine the relationship between bio-physiology of the body (measured by the glycated hemoglobin level of HbA1c) and the emotional situation and adherence to OAD. Observational research with a cross-sectional approach was carried out on 76 type 2 diabetics who were treated at the Gotong Royong Hospital (RSGR) Surabaya. Research data was taken through a valid and reliable questionnaire about emotional situation and adherence to OAD. The glycated hemoglobine was measured in the RSGR laboratory. Inferential analysis was tested using Spearman correlation test. The results showed a significant negative correlation power between the emotional situation and the level of HbA1c (r = -0.256, p = 0.026), as well as between the level of adherence to OAD and the level of HbA1c (r = -0.402, p = 0.000). Those outcomes indicated that the more positive the emotional situation, as well as the higher the level of adherence to OAD, the better health outcome of the diabetic patient. These results enrich the educational material in health promotion. Enhancing the positive emotional situation and the level of adherence to OAD will decrease the morbidity and mortality rates due to diabetes, and optimize the welfare of the patient.